Health economics - Sloan, Frank A.; Hsieh, Chee-Ruey (London The MIT Press, 2016)
Health economics is the study of how to efficiently allocate scarce resources in healthcare, focusing on costs, outcomes, and behaviors to improve health systems' effectiveness, equity, and accessibility for all, analyzing everything from individual patient choices and provider efficiency to public health policies and insurance impacts.